Recent Advances in the Grain Refinement Effects of Zr on Mg Alloys: A Review - Ming Sun; Depeng Yang; Yu Zhang; Lin Mao; Xikuo Li; Song Pang (Metals, 2022)
As the lightest structural materials, Mg alloys show great effectiveness at energy saving and emission reduction when applied in the automotive and aerospace fields. In particular, Zr-bearing Mg alloys (non-Al containing) exhibit high strengths and elevated-temperature usage values. Zr is the most powerful grain refiner, and it provides fine grain sizes, uniformities in microstructural and mechanical properties and processing formability for Mg alloys. Due to the importance of Zr alloying, this review paper systematically summarizes the latest research progress in the grain refinement effects of Zr on Mg alloys. The main points are reviewed, including the alloying process of Zr, the grain refinement mechanism of Zr, factors affecting the grain refinement effects of Zr, and methods improving grain refinement efficiency of Zr. This paper provides a comprehensive understating of grain refinement effects of Zr on Mg alloys for the researchers and engineers.